Recomendaciones CODEPEH 2014 - Núñez Batalla, Faustino; Jáudenes Casaubón, Carmen; Sequí Canet, Jose Miguel; Vivanco Allende, Ana; Zubicaray Ugarteche, José (Revista Española de Discapacidad, 2015)
Núñez, F. et al. (2015): “Recomendaciones CODEPEH 2014”, Revista Española de Discapacidad, 3 (1): 163-186.